ATP-Binding Cassette Genes Genotype and Expression: A Potential Association with Pancreatic Cancer Development and Chemoresistance? - Li Pang; Beverly Word; Joshua Xu; Honggang Wang; George Hammons; Shiew-Mei Huang; Beverly Lyn-Cook (Gastroenterology Research and Practice)
Genetic polymorphisms in ABC (ATP-binding cassette) transporter genes are associated with differential responses to chemotherapy in various cancers including pancreatic cancer. In this study, four SNPs in the ABCB1, ABCC1, and ABCG2 genes were investigated in normal and pancreatic cancerous specimens. The expression of the three transporters was also analyzed. The TT genotypes of G2677T and C3435T in ABCB1 gene were associated with lower risk of developing pancreatic cancer (P=0.013, OR = 0.35 and P=0.015, OR = 0.29, resp.). To our knowledge, this is the first report of the common polymorphisms in the ABCB1 gene affecting the genetic risk of developing pancreatic cancer. Moreover, the expression of ABCB1 in 2677TT and 3435TT carriers was lower compared to the wild-type homozygotes and heterozygotes. A cell viability assay, using standard pancreatic cancer cell lines, revealed that the ABCB1 2677TT-3455TT haplotype was more sensitive than the other haplotypes to gemcitabine. Conclusion. Polymorphisms in ABCB1 G2677T and G3435T were associated with differential susceptibility to pancreatic cancer and may predict responses to chemotherapy.